Benzo[b]thiophene-2-carboxamide derivatives as potent urotensin-II receptor antagonists. Issue 19 (1st October 2016) - Lim, Chae Jo; Woo, Seong Eun; Ko, Su Ik; Lee, Byung Ho; Oh, Kwang-Seok; Yi, Kyu Yang
Graphical abstract: Abstract: Members of a series of benzo[ b ]thiophene-2-carboxamide derivatives, possessing an N -(1-(3-bromo-4-(piperidin-4-yloxy)benzyl)piperidin-4-yl) group, were synthesized and evaluated as urotensin-II receptor antagonists. The results show that these substances have potent UT binding affinities. Observations made in a systematic SAR investigation of the effects of a variety of substituents (R 1 and R 2 ) at the 5- and 6-positions in the benzo[ b ]thiophene-2-carboxamide moiety on UT binding affinities led to identification of the 5-cyano analog7f as a highly potent UT antagonist with an IC50 value of 25 nM. Despite having a good metabolic stability, 7f is a potent inhibitor of CYP isozyme and displays an unsuitable PK profile.